2000
DOI: 10.1086/301440
|View full text |Cite
|
Sign up to set email alerts
|

The Central Gas Systems of Early-Type Galaxies Traced by Dust Features, Based on the [ITAL]HUBBLE SPACE TELESCOPE[/ITAL][ITAL]Hubble Space Telescope[/ITAL] WFPC2 Archival Images

Abstract: We investigated the central gas systems of E/S0 galaxies by making use of the WFPC2 images of the Hubble Space Telescope archive. We searched the gas systems that were traced by the dust with a new method of making color excess images in F 555W − F 814W (V − I). Out of 25 sample galaxies, we detected gas system in 14 galaxies. The dust was newly detected in two galaxies that were thought to contain no dust based on single band, pre-refurbishment data. The full extents of the gas systems are 0.1 to 3.5 kpc, and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
76
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(81 citation statements)
references
References 15 publications
(34 reference statements)
5
76
0
Order By: Relevance
“…An irregular dust distribution is present in the nuclear region of IC 1459 (Goudfrooij et al, 1990). Although on average this provides too little reddening [E(B-V)=0.07, or 4×10 20 cm −2 for standard dust to gas ratio and composition] to hide an AGN, the obscuration could well be much greater near the nucleus (Tomita et al 2000). In this case, however, we would expect to see the 'missing' luminosity in the infrared.…”
Section: Hiding the Emission: Obscurationmentioning
confidence: 96%
“…An irregular dust distribution is present in the nuclear region of IC 1459 (Goudfrooij et al, 1990). Although on average this provides too little reddening [E(B-V)=0.07, or 4×10 20 cm −2 for standard dust to gas ratio and composition] to hide an AGN, the obscuration could well be much greater near the nucleus (Tomita et al 2000). In this case, however, we would expect to see the 'missing' luminosity in the infrared.…”
Section: Hiding the Emission: Obscurationmentioning
confidence: 96%
“…Veron-Cetty & Veron 1988;van den Bergh & Pierce 1990;Michard 1999), although already Bregman & Roberts (1990) reported extended dust features ≈100 east from a private communication by J. L. Tonry. After a first non-detection of dust in the very center of M 86 (Tomita et al 2000), a central dusty disk has eventually been found by Tran et al (2001).…”
Section: Introductionmentioning
confidence: 99%
“…, (13) Nikołajuk & Walter (2013), (14) Tomita et al (2000), (15) Nicholson et al (1997), (16) Elmegreen et al (1998), and (17) Randall et al (2009 …”
mentioning
confidence: 99%